2022
DOI: 10.1371/journal.pone.0278622
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Monkeypox vaccination and predictors of vaccination intentions among the US general public

Abstract: Amidst an unprecedented Monkeypox outbreak, we aimed to measure knowledge, attitudes, practices and Monkeypox vaccination intentions among the U.S. adult population. We conducted an online cross-sectional survey, representative of the U.S. adult general public in June 2022. We asked participants whether they would receive a Monkeypox vaccine, if they were recommended to do so. Participants also answered questions on their self-assessed level of Monkeypox knowledge, risk perception, perceived exaggeration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 30 publications
2
40
2
Order By: Relevance
“…The 60.5% adequate knowledge found in this study is lower than the 70% good knowledge found among Jordanian healthcare students [ 35 ]. However, the 60.5% adequate knowledge is higher than 48% among the general population in Saudi Arabia [ 32 ], 36.6% in Indonesian general healthcare practitioners [ 36 ], 27% among Italian medical professionals [ 37 ] and 47% found among the general public in the US [ 38 ]. Similarly, the overall knowledge score of 4.8 found in this study is higher than 3.8 reported in Kuwait [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 60.5% adequate knowledge found in this study is lower than the 70% good knowledge found among Jordanian healthcare students [ 35 ]. However, the 60.5% adequate knowledge is higher than 48% among the general population in Saudi Arabia [ 32 ], 36.6% in Indonesian general healthcare practitioners [ 36 ], 27% among Italian medical professionals [ 37 ] and 47% found among the general public in the US [ 38 ]. Similarly, the overall knowledge score of 4.8 found in this study is higher than 3.8 reported in Kuwait [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, satisfactory knowledge and positive attitude towards MPOX vaccination can affect HCWs’ recommendation of the vaccine for other high-risk groups (e.g., men who have sex with men (MSM)) [ 28 , 40 ]. Specifically, and in the context of MPOX vaccination intention among the general public in the U.S., Winters et al reported that the most trusted sources of information regarding the outbreak were HCWs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk perception and normative beliefs are associated with vaccination intention 21–24 . A study conducted on the US population to examine the Mpox vaccination attitudes of the participants revealed that those with the highest risk perception appeared to be more interested in receiving the vaccination 20 . During the Covid‐19 pandemic, people severely affected by the coronavirus showed agreement with vaccination acceptance 37–39 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, participants assumed to be at the highest risk had a favorable attitude toward vaccination, 42–45 whereas people with lower risk perceptions had lower vaccination intentions, according to a few additional studies 43,46 . A study conducted among clinicians in the United States stated that participants who perceived a higher risk perception of Mpox were more likely to be ready to receive the vaccine, and they were concerned about the people who did not consider Mpox a severe risk as they were less likely to be interested in vaccination uptake 20 . People in the United States with a higher risk perception wanted to get vaccinated against COVID‐19 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation